Characterization of surface crack width in plates using Rayleigh wave electromagnetic acoustic transducers. Issue 4 (January 2021) - Ahmad, Mubarak; Liu, Zenghua; Basit, Abdul; Bin, Wu; He, Cunfu
Abstract: Surface crack in the plate like structures is one of the initial indication for its degradation. This indication could be very critical and requires some serious maintenance because this continuous exposure will lead to a severe damage to the safety and even to environment. To evaluate the structural performance and safety, a regular monitoring of such cracks is needed. A quantitative characterization method is utilized for the estimation of surface groove width instead of depth or length, which is previously done by many researchers, using Rayleigh waves in pitch-catch mode using electromagnetic acoustic transducers (EMATs). The method employs the experimentally determined reflection coefficient and transmission coefficient of Rayleigh waves scattered at a surface groove by a number of varying widths, which are compared to the reference curves, obtained from two-dimensional finite element method (2D-FEM) simulations for the same groove width as used in experiments. A good relation between FEM results and experimental results is found. Two different EMAT couples of different centre frequencies were employed to explore the measurement, and to compare and analyse the quantitative characterization of different groove widths. Both the FEM results and experimental results are compared and verified for the different groove widths. This comparison shows some percentage of error for the groove width ranging from 0.3 mm to 1.8 mm.